2008
DOI: 10.1002/mrm.21887
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional spatial and temporal temperature control with MR thermometry‐guided focused ultrasound (MRgHIFU)

Abstract: High-intensity focused ultrasound (HIFU) is an efficient noninvasive technique for local heating. Using MRI thermal maps, a proportional, integral, and derivative (PID) automatic temperature control was previously applied at the focal point, or at several points within a plane perpendicular to the beam axis using a multispiral focal point trajectory. This study presents a flexible and rapid method to extend the spatial PID temperature control to three dimensions during each MR dynamic. The temperature in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
93
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 128 publications
(94 citation statements)
references
References 22 publications
0
93
0
1
Order By: Relevance
“…Treatment optimisation to improve clinical outcome is an important application, but because of the uncertainties in tissue properties treatment limiting hot spots might still occur after pre-treatment optimisation. Some research groups explore the possibility to combine treatment planning with MRI feedback [81][82][83], but this requires MR-compatibility of the heating system. Therefore also on-line adaptive use of treatment planning is currently investigated [84][85][86].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment optimisation to improve clinical outcome is an important application, but because of the uncertainties in tissue properties treatment limiting hot spots might still occur after pre-treatment optimisation. Some research groups explore the possibility to combine treatment planning with MRI feedback [81][82][83], but this requires MR-compatibility of the heating system. Therefore also on-line adaptive use of treatment planning is currently investigated [84][85][86].…”
Section: Discussionmentioning
confidence: 99%
“…Histological examinations of the skeletal muscles in pigs have showed that the minor damage can occur at 30 CEM 43 [25]. A thermal dose scale of 240 CEM 43 has been established for the leg muscles of rabbits and pigs and this dose is an irreversible lethal dose to the tissue cells [26][27][28]. In the implanted group, the results revealed that the temperature increases in the muscles in front of the titanium alloy implants were less than 41°C.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated for different resolutions and FOVs that increased TE (18-34 ms) can be achieved with multislice coverage (4-6 slices) and short acquisition times (∼0.5-3 s) using segmented echo-planar imaging (EPI) approaches. [51][52][53] Nonetheless, the MR thermometry sequence implemented for this study enabled us to implement multiplanar temperature control for transurethral ultrasound therapy and achieve successful treatments of whole-prostate volumes with geometries that are representative of what would be encountered clinically. This study highlighted the important roles of frequency and power for transurethral ultrasound therapy.…”
Section: Discussionmentioning
confidence: 99%